An antibonding valence band maximum enables defect-tolerant and stable GeSe photovoltaics - Shun-Chang Liu (Nature Portfolio, 2021)
Perovskite-like antibonding VBM electronic structure is predicted to result in defect-tolerant materials. Here, the authors investigate GeSe with antibonding VBM from Ge 4s-Se 4p coupling, and a certified 5.2% PCE is obtained with high stability due to its strong covalent bonding.